Effect of steel and synthetic fibers on shear strength of RC beams without shear stirrups. (15th May 2015) - Sahoo, Dipti Ranjan; Maran, Kaushik; Kumar, Avdhesh
Highlights: Polypropylene fiber reinforced concrete beams exhibited reduced shear strength. Combined fiber reinforced concrete beams exhibited multiple shear cracks. A minimum of 0.5% of steel and polypropylene fibers can replace the stirrups. Both steel and polypropylene fibers of 1% can improve the shear strength. Abstract: This study presents the influence of the type and volume fraction of fibers in the concrete mix on the shear strength of RC beams. One RC (control) and six fiber reinforced concrete (FRC) beam specimens are tested under the gradually increasing monotonic loading. Both high-modulus (steel) and low-modulus (polypropylene) fibers of either 0.5% and 1% volume fraction in concrete are used in FRC specimens. Shear stirrups are completely eliminated in the half-span of the FRC specimens. A better post-peak residual strength response is noticed in case of all FRC beam specimens due to multiple cracking associated with the fiber bridging action. The main parameters investigated are shear strength, failure mechanism and displacement ductility. In the absence of shear stirrups, the peak shear resistance and mid-span displacement of the FRC specimen 1% of polypropylene fibers only reached about 70% and 50% of corresponding values for the RC specimen. The FRC specimens with combined steel and polypropylene fibers of minimum volume fraction of 0.5% in the concrete reached the same shear strength as RC specimen in the absence of shear stirrups. However, the shear resistance and deformability values are improved by 20% and 40%, respectively, when the polypropylene fibers of 1% of volume fraction were added to the concrete in addition to the steel fiber of 1% fiber content. Further, multiple cracks of smaller crack width are noticed at the failure stage of the CFRC specimens indicating the better fiber bridging action of combined metallic and nonmetallic fibers.